Can guava (Psidium guajava) leaf extracts develop an indigenous, simplified tool for a semi-quantitative assessment of iron in groundwater?. (18th October 2022) - Rahman, Sabuktagin; Saha, Nobonita; Sarwar, Sneha; Shamim, Abu Ahmed; Shaheen, Nazma
Abstract: Iron present in the drinking groundwater is attributed to the low burden of iron deficiency (ID) in Bangladesh. The supplemental anemia prevention strategies involving iron need a cautious approach due to the excess load of iron and the side effects. The present pilot study examined the potential of the guava leaf extracts to use as a natural reagent for the assessment of iron in groundwater. Eighteen households with the drinking source of groundwater were randomly selected. Guava leaves were crushed and the shreds of the leaves were mixed with the water sample. Changes of water color were photographed. Five groups were identified – 'whitish', 'shades of pink', 'shades of purple', 'light black' and the 'frank black'. The iron concentration was measured by a test kit device. Each color group was assigned a number on the ordinal scale 1–5. Statistical correlation and agreements were performed between the methods. The positive correlation (Kendall's tau b : 0.89, p < 0.000) and the agreements (Kappa: 0.77, p < 0.000; rho_c: 0.73, p < 0.000) were observed. Guava leaf extracts may standardize an indigenous tool for a semi-quantitative measurement of groundwater iron content. Validation of the tool thus may aid in the design and evaluation of the iron supplementation and fortification programs. HIGHLIGHTS: In a largely iron-replete population, iron supplementation programs need a cautious approach to limit side effects. Guava leaf extract by changing the color of the iron-rich groundwater concurs with the colorimetric iron testing. Guava leaf extract may standardize an indigenous tool for the measurement of groundwater iron content. Validation of the tool may aid the design of the anemia programs, promoting public health. Graphical Abstract